HCC with low- and normal-serum alpha-fetoprotein levels - Carr, Brian I. (Clin Pract (Lond), 2018)
A large database of 1773 HCC patients in Turkey was examined. 41.9% had alpha-fetoprotein (AFP) levels <20 IU/ml and an additional 16.123% had values between 20–100 IU/ml. This 58% of the cohort (<100 IU/ml AFP levels) was examined in detail. 66% of patients with small (<5 cm) HCCs had low AFP, compared to 49% of patients with larger (>5 cm) HCCs. The mean diameter (MTD) of larger MTD, low AFP tumors was 8.4cm. Therefore, factors other than AFP must contribute to HCC tumor growth. Larger tumors in low AFP patients had both higher platelet levels and increased PVT percent. Linear regression analysis for both MTD and multifocality showed that platelet numbers and presence of PVT were significant variables; whereas for PVT, significant variables were albumin, alkaline phosphatase and MTD. Comparisons between patients with AFP levels <20, 20–<100, 100–<1000 and >1000 IU/ml showed the most significant tumor finding was an increase in PVT percent between each group, and to a lesser extent, MTD. Thus, low- or normal-AFP HCCs constitute the majority of patients and have slightly lower MTD and much lower PVT percent than HCCs associated with elevated blood AFP levels. New, non-AFP markers are thus needed, especially for small HCCs